Iacta Alea Est: The Inexorable Advance of Tofacitinib in the Treatment of Dermatomyositis-Associated Rapidly Progressive Interstitial Lung Disease. A Case Report - Conca, Walter; Weheba, Ihab; Abouzied, Mohei-Eldin; Abdelsayed, Abeer; Aleyouni, Yousif; Al‐Mutairy, Eid; Bakshi, Nasir; Khalid, Mohammad (Frontiers in Pharmacology, 2020)
Rapidly progressive interstitial lung disease is typically associated with clinically amyopathic dermatomyositis and the anti-melanoma differentiation associated gene 5 antibody, a condition with high mortality and resistance to classic immunosuppression. Recent reports have described the efficacy of the Janus kinase inhibitor tofacitinib in the treatment of rapidly progressive interstitial lung disease in anti-melanoma differentiation associated gene 5 antibody-positive clinically amyopathic dermatomyositis. It is uncertain, however, whether tofacitinib alters the course of rapidly progressive interstitial lung disease in other variants of dermatomyositis that are unrelated to the anti-melanoma differentiation associated gene 5 antibody and whether the early addition of the anti-fibrotic tyrosine kinase inhibitor nintedanib interferes with the development of fibrosis. To answer these questions, we present and discuss the case of an elderly woman who presented with a flare of dermatomyositis sine myositis. Based upon the detection of anti-Jo-1 antibodies and the absence of anti-melanoma differentiation associated gene 5 antibodies, anti-synthetase syndrome was diagnosed. While the cutaneous manifestations quickly resolved with prednisone, azathioprine and tacrolimus, the respiratory function paradoxically and rapidly deteriorated, and invoked the use of tofacitinib. Markedly raised ferritin levels and a severe numerical deficiency of circulating natural killer cells paralleled the acute lung inflammation, which was reflected by 18F-fluorodeoxyglucose hypermetabolism on positron emission tomography/CT. Tofacitinib lead to a prompt clinical recovery, with a reduction in oxygen requirement, correction of hyperferritinemia, reversal of the natural killer cell deficiency, and a decrease in 18F-fluorodeoxyglucose uptake in the affected lung segments. Subsequently, nintedanib was added at a point in time when inflammation subsided. Apart from cytomegalovirus reactivation no adverse events occurred. In conclusion, tofacitinib reversed the pronounced inflammatory component of anti-Jo-1 antibody-positive, anti-melanoma differentiation associated gene 5 antibody-negative rapidly progressive interstitial lung disease, confirming that Janus kinase signaling pathways are critically involved in the pathogenesis of rapidly progressive interstitial lung disease, apparently independently of the targeted autoantigen. Although some improvement in pulmonary function was observed, it seems premature to conclusively judge on reversibility or prevention of pulmonary fibrosis by pairing both kinase inhibitors for which an extended follow-up and ideally, prospective and controlled studies are needed.